Cyclic-loading of the human gracilis and semitendinosus muscle tendons: Study of young adult cadavers - Piedade, Sergio Rocha; Dal Fabbro, Inacio Maria; Mischan, Martha Maria (Blackwell Publishing, 2006)
During knee ligament reconstruction, the tendon graft is tensioned to prevent the occurrence of excessive graft elongation during the postoperative period. Tensioning may be achieved by applying a cyclic or static load to the graft during fixation. Although this procedure is part of the surgery, there is no consensus in international literature regarding ideal tension levels to be used in this procedure. This study was conducted on 10 tendons of the human gracilis muscle and 10 tendons of semitendinosus muscle removed from five male cadavers whose mean age was 20.8 years. These tendons underwent 10 in vitro strain cycles at three levels of deformation (2.5, 3, and 4%) and the value of the deforming load used for each cycle was recorded. The statistical analysis demonstrated that in order to attain the same level of deformation during the 10 cycles there was a reduction in the value of strain applied to the graft, observed at the three levels of deformation. It was concluded that the semitendinosus tendon presents a more uniform mechanical behavior and that there is a need for new graft tensioning protocols that consider the force associated with deformation.
Keywords: tendons; biomechanics; stress relaxation